DISSEMINATED BACILLUS-CALMETTE-GUÉRIN INFECTIONS AND PRIMARY IMMUNODEFICIENCY DISORDERS IN SINGAPORE: A SINGLE CENTER 15-YEAR RETROSPECTIVE REVIEW. (August 2020) - Ong, Rina Yue Ling; Chan, Su-Wan Bianca; Chew, Siu Jun; Liew, Woei Kang; Thoon, Koh Cheng; Chong, Chia-Yin; Yung, Chee Fu; Sng, Li-Hwei; Tan, Ah Moy; Bhattacharyya, Rajat; Jamuar, Saumya Shekhar; Lim, Jiin Ying; et al.
Highlights: Fever, cutaneous lesion, lymphadenopathy, musculoskeletal pain, and hepatosplenomegaly were the most common signs and symptoms of disseminated Bacillus Calmette-Guérin infection. The two main underlying diagnoses of primary immunodeficiency disorders were Mendelian Susceptibility to Mycobacterial Diseases (MSMD) and Severe Combined Immunodeficiency (SCID). Low-level isoniazid resistance may not correspond to clinical resistance, as sufficient drug concentrations are attained, and high-dose isoniazid is not required. The three-drug regimen of rifampicin, ethambutol, and a fluoroquinolone, or rifampicin, ethambutol, and isoniazid are suitable empiric first-line therapies. Abstract: Background: Disseminated Bacillus Calmette-Guérin (BCG) disease (BCGosis) is a classical feature of children with primary immunodeficiency disorders (PIDs). Methods: A 15-year retrospective review was conducted in KK Women's and Children's Hospital in Singapore, from January 2003 to October 2017. Results: Ten patients were identified, the majority male (60.0%). The median age at presentation of symptoms of BCG infections was 3.8 (0.8 – 7.4) months. All the patients had likely underlying PIDS – four with Severe Combined Immunodeficiency (SCID), three with Mendelian Susceptibility to Mycobacterial Diseases (MSMD), one with Anhidrotic Ectodermal Dysplasia with Primary Immunodeficiency (EDA-ID), one with combined immunodeficiency (CID), and one with STAT-1 gain-of-function mutation. Definitive BCGosis was confirmed in all patients by the identification of Mycobacterium bovis subsp BCG from microbiological cultures. The susceptibility profiles of Mycobacterium bovis subsp BCG are as follows: Rifampicin (88.9%), Isoniazid (44.47%), Ethambutol (100.0%), Streptomycin (100.0%), Kanamycin (100.0%), Ethionamide (25.0%), and Ofloxacin (100.0%). Four patients (40.0%) received a three-drug regimen. Five patients (50.0%) underwent hematopoietic stem cell transplant (HSCT), of which three (60%) have recovered. Overall mortality was 50.0%. Conclusion: Disseminated BCG disease (BCGosis) should prompt immunology evaluation to determine the diagnosis of the immune defect. A three-drug regimen is adequate for treatment if the patient undergoes early HSCT.